In vitro anti-venom potential of various Jatropha extracts on neutralizing cytotoxic effect induced by phospholipase A2 of crude venom from Indian cobra (Naja naja) - Reddi, K. V. N. Rathnakar; Rajesh, Sivarathri Siva; Narendra, Kumara; Jangala, Swathi; Reddy, Puli Chandra Obul; Satya, Alapati Krishna; Sivaraman, Thirunavukkarasu; Sekhar, Akila Chandra (Bangladesh Journal of Pharmacology, 2014)
In present study various species of Jatropha were evaluated for antidote nature induced by phospholipase A2 (PLA2) cobra venom. Although qualitative phytochemical analysis exhibited less variation across Jatropha species studied, substantial variability in terms of PLA2 inhibition by various solvent extracts across the species and between different parts of same plant was observed. Among all samples methanolic extracts of J. gossypifolia leaf showed highest inhibition of PLA2 toxicity while some aqueous extracts of J. foetida and all aqueous extracts of J. curcas, enhanced PLA2 activity. Present results highlight Jatropha not only as rich source of secondary compounds with antidote property for snake bite but also potent toxic agents as revealed with increased hemolysis by some aqueous extracts of J. curcas and J. foetida. Our findings suggest that methanolic leaf extract of J. gossypifolia contain potent small molecular antagonist(s) to the snake venom PLA2 which will be very useful to design adjuvant therapies in treatments of snake bites.